Genomic Insights Into Clinical Shiga Toxin-Producing Escherichia coli Strains: A 15-Year Period Survey in Jönköping, Sweden - Bai, Xiangning; Zhang, Ji; Hua, Ying; Jernberg, Cecilia; Xiong, Yanwen; French, Nigel; Löfgren, Sture; Hedenström, Ingela; Ambikan, Anoop; Mernelius, Sara; Matussek, Andreas (Frontiers in Microbiology, 2021)
Shiga toxin-producing Escherichia coli (STEC) are important foodborne pathogens which can cause human infections ranging from asymptomatic carriage to bloody diarrhea (BD) and fatal haemolytic uraemic syndrome (HUS). However, the molecular mechanism of STEC pathogenesis is not entirely known. Here, we demonstrated a large scale of molecular epidemiology and in-depth genomic study of clinical STEC isolates utilizing clinical and epidemiological data collected in Region Jönköping County, Sweden over a 15-year period. Out of 184 STEC isolates recovered from distinct patients, 55 were from patients with BD, 129 were from individuals with non-bloody stools (NBS). Five individuals developed HUS. Adults were more associated with BD. Serotypes O157:H7, O26:H11, O103:H2, O121:H19, and O104:H4 were more often associated with BD. The presence of Shiga toxin-encoding gene subtypes stx2a, stx2a+stx2c, and stx1a+stx2c was associated with BD, while stx1a was associated with milder disease. Multiplex virulence and accessory genes were correlated with BD, these genes encode toxins, adhesion, autotransporters, invasion, and secretion system. A number of antimicrobial resistance (AMR) genes, such as aminoglycoside, aminocoumarin, macrolide and fluoroquinolone resistance genes, were prevalent among clinical STEC isolates. Whole genome-phylogeny revealed that O157 and non-O157 STEC isolates evolved from distinct lineages with a few exceptions. Isolates from BD showed more tendency to cluster closely. In conclusion, this study unravels molecular trait of clinical STEC strains, and identifies genetic factors associated with severe clinical outcomes, which could contribute to management of STEC infections and disease progression if confirmed by further functional validation.